Prevalência de neoplasias malignas em região oral e maxilofacial oriundas do laboratório de patologia da Universidade Federal do Amazonas: casuística de 30 anos - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Introduction: Oral cancer can be defined as a malignant neoplasm that originates in the tissues that will develop the oral cavity. Worldwide malignant neoplasms of the mouth occupy the sixth place among the most common cancers. In Brazil it is considered the seventh most common type of cancer, showing high mortality rates in the country. The similarity between the neoplasms that can occur in this region, makes the diagnosis a daily challenge for health professionals. Objective: To evaluate the prevalence of malignant neoplasms involving the oral and maxillofacial region (OMF) diagnosed in the Laboratory of Pathology of the Federal University of Amazonas (UFAM) for a period of 30 years, between January 1987 and December 2016. Methodology: a cross-sectional, retrospective study, where the records of requesting exams and/or medical records, data concerning the patient, such as age, gender and race were analyzed, as well as those referring to the actual injury, such as location and anatomical region, clinical characteristics and the histopathological diagnosis of the lesion. Data were processed and submitted to Fisher's exact test. Results: A total of 62,005 reports were analyzed, of which 3,45% (n=2140) were in the oral and maxillofacial regions, and 4,7% (n=101) represented malignant neoplasms in the OMF region. The most frequent malignant neoplasms were those of epithelial tissue with 77,2% (n=78) of the cases, especially squamous cell carcinoma (SCC) (61,38%, n=62). The remaining cases were neoplasms of mesenchial tissue (6,9%, n=7), glandular (10,9%, n=11) and hematolymphoid (5,0%, n=5). No cases of malignant neoplasms of odontogenic tissue were found. Regarding the age range, the highest number of cases occurred in patients over 50 years of age, with a prevalence peak between 51-60 (21,8%, n=22), patients aged 0-10 years represented the group of lower involvement (2,0%, n=2). Brown individuals were the most frequently affected (25,7%, n=26), followed by whites (12,9%, n=13) and blacks (4,0%, n=4). Of the 101 lesions found 94.1% (n=95) were primary neoplasms and 5,0% (n=5) of metastatic lesions. Conclusion: malignant neoplasms at the OMF region represented a small fraction among the large number of diseases that can occur in these tissues. The literature appoints the SCC as the most common malignant neoplasm in the mouth, in agreement with that found in the present study.
Keywords: Câncer de boca; Patologia bucal; Epidemiologia; Neoplasia; CIÊNCIAS DA SAUDE: ODONTOLOGIA